The automation of the CommGroup Training Library - Salas, Jody C.; Santos, Herminia H. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2001)
The Communication Group Training is responsible for giving skill training and other seminars, both technical and non-technical to the Lopez Group of Companies, composing of BayanTel, ABS-CBN and Sky Cable. On the average, they conduct daily training to more than fifty employees. Thus, it is valuable for them to have fast access to training materials especially during preparation for a scheduled training. The CommGroup Training Library supports the curricular and instructional programs of the department. The library boasts of an extensive collection of print materials including books, periodicals, training materials and multi-media sources like videotapes.
The researcher created a database of the library materials and automated the CommGroup Training Library retrieval system using MS Access 2000. The researcher also utilized the use of Local Area Network, to allow users to access the database from their work desks.
The search results of library users improved dramatically in terms of speed of acquisition, accuracy of materials acquired, and ease of using the library. Results showed that in terms of speed of acquisition, the automated retrieval system saves 180-440 minutes on all twenty queries, as compared to manual searching. Regarding the Recall Ratio, it was derived using Lancaster's (1968) formula of dividing the number of relevant materials retrieved over the total number of materials retrieved. The result was 47.4 percent for manual searching, and 76 percent using the automated retrieval system.
On a scale of one to five, having 1 as extremely easy to use, 2 as easy, 3 as difficult, 4 as extremely difficult, and 5 as not library practical. The automated retrieval system was rated 1.30 as compared to 3.85 on manual searching. Although there is a relatively low decline of the Precision Ratio from 87 percent through manual searching, to 76 percent with the aid of retrieval system, the researcher analyzed that the margin of time and energy spent to access the same materials was extensive. The researcher concludes that the automated retrieval system for the CommGroup Training Library has greatly improved its retrieval process, by making it more efficient and economical in terms of time and energy.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Special libraries -- Automation. -- Philippines